The Degree of Capillary Absorption Reduction as a Parameter to Classify the Effectiveness of Secondary Horizontal Waterproofing - Monczyński, Bartłomiej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The dampness of the ground floors in buildings is generally a consequence of capillary rise of groundwater caused by the absence, damage or technical deterioration of the horizontal waterproofing of the masonry. Capillary absorption and damp transport are determined by the wetting properties of water relative to the material, as well as the structure and distribution of pores in the material. Chemical (injection) methods of secondary horizontal waterproofing are based on the technology of introducing injection liquid into the masonry section, which forms a lock which relies on the mechanism of capillary lumen constriction, hydrophilization, capillary sealing or a combined effect.
Keywords: absorption; capillary rise; dampness; effectiveness; injection; waterproofing